Β-Sitosterol inhibits ovalbumin-induced asthma-related inflammation by regulating dendritic cells. (2nd November 2022) - Wang, Ru; Zeng, Mengnan; Zhang, Beibei; Zhang, Qinqin; Jia, Jufang; Cao, Bing; Liu, Meng; Guo, Pengli; Zhang, Yuhan; Zheng, Xiaoke; Feng, Weisheng
Abstract: Aim: To investigate the effects of β-sitosterol (B-SIT) and the underlying mechanisms of action in an ovalbumin-induced rat model of asthma. Methods: The pathological and morphological changes in lung and tracheal tissues were observed by H&E, PAS, and Masson's staining. The levels of IgE, TNF- α, and IFN- γ in the bronchoalveolar lavage fluid (BALF) and those of IL-6, TGF-β1, and IL-10 in serum were measured by ELISA. The relative expression levels of IL-5, IL-13, IL-21, CD11c, CD80, and CD86 mRNA in lung tissue were examined by RT-qPCR. Flow cytometry was performed to assess the levels of immune cells, including macrophages and neutrophils in spleen tissue and Th cells, Tc cells, NK cells, and DCs in peripheral blood. The protein expression levels of CD68, MPO, CD11c, CD80, and CD86 were detected by western blotting or immunohistochemistry. Results: B-SIT improved the injury in OVA-induced pathology, decreased the levels of inflammatory factors of IgE, TNF- α, IL-6, TGF-β1, IL-5, IL-13, and IL-21 and increased the levels of IFN-γ and IL-10. In addition, B-SIT decreased the number of macrophages and neutrophils and the relative expression levels of CD68 and MPO in the spleen. Moreover, B-SIT increased the number of Th cells, Tc cells, NK cells, and DCs in peripheral blood and upregulated the levels of CD11c, CD80, and CD86 in the spleen and lung. Conclusion: B-SIT improved symptoms in a rat model of asthma likely via the inhibition of inflammation by regulating dendritic cells.